Pengaturan Suhu Tubuh dengan Metode Tepid Water Sponge dan Kompres Hangat pada Balita Demam - NLP Yunianti SC; Putu Susy Natha Astini; Ni Made Desi Sugiani (Politeknik Kesehatan Tanjung Karang, 2019)
Fever is a condition of an increase in body temperature. High fever can cause many complications. The purpose of this research was to know the difference of effectiveness of tepid water sponge and warm compress method to control the body in children under five years having a fever. This research was used quasi-experimental design and non-equivalent control group design. The number of samples in each group was 30 people selected by consecutive sampling technique. The result of the average temperature drop in the tepid water sponge group was 0.9930C, while the average temperature drop in the warm compress group was 0,540C. The result of this research was used paired-samples t-test and independent-samples t-test and obtained p-value=0.0001 (p<0.05). There was a difference of effectiveness of tepid water sponge and warm compress method to control the body temperature in children under five years with fever at Puskesmas Abiansemal I and Puskesmas Mengwi I Year 2018.